Dectin-1 Is expressed in human lung and mediates the proinflammatory immune response to nontypeable haemophilus influenzae - Heyl, Kerstin Andrea; Klassert, Tilman E.; Heinrich, Annina; Müller, Mario M.; Klaile, Esther; Dienemann, Hendrik; Grünewald, Christiane; Bals, Robert; Singer, Bernhard B.; Slevogt, Hortense (mBio, 2014)
The C-type lectin receptor Dectin-1 is expressed mainly on myeloid cells mediating the immune response targeting respiratory pathogens such as Aspergillus fumigatus and Mycobacterium tuberculosis. The pulmonary epithelium serves as an important interface for interactions between these pathogens and the respiratory tract. Therefore, we analyzed the expression pattern of Dectin-1 in the human lung. Immunohistochemically stained human lung sections from 17 out of 19 individuals were positive for Dectin-1, which was expressed mainly apically on bronchial and alveolar epithelium. Our results showed no correlation with chronic obstructive pulmonary disease (COPD) or the smoking habits of the patients. Nontypeable Haemophilus influenzae (NTHI), an important bacterial pathogen of the respiratory tract with significant importance in COPD, has also been proposed to be recognized by Dectin-1, suggesting a possible impact on the NTHI-dependent immune response in human airways. Therefore, the involvement of Dectin-1 in NTHI-triggered cytokine responses was investigated in primary normal human bronchial epithelial (NHBE) cells and in the A549 cell line stably transfected with Dectin-1. The presence of Dectin-1 significantly increased cytokine release in response to NTHI in NHBE and A549 cells. In addition, phosphorylation of the Dectin-1 hem-immunoreceptor tyrosine-based activation motif (hemITAM) was essential for the Dectin-1-triggered response to NTHI in A549 cells. In conclusion, in human airways, epithelium-expressed Dectin-1 may play a significant role in generating an NTHI-mediated, proinflammatory immune response. - IMPORTANCE In this study, we demonstrated, for the first time, the expression of Dectin-1 on human lung tissues and, in particular, pulmonary epithelium by making use of immunohistochemical staining. The epithelial lining of the human airways is an important interface for host-pathogen interactions. Therefore, our data suggest that epithelium-expressed Dectin-1 is of considerable importance for the interaction of the human airways with pathogens detected by this receptor, such as A. fumigatus and M. tuberculosis. Moreover, we further demonstrated that, in pulmonary epithelial cells, Dectin-1 enhances the proinflammatory immune response to NTHI. In COPD patients, NTHI is a major cause of respiratory tract infections and is associated with proinflammatory immune responses in the lower airways. Therefore, our data suggest that the functional interaction of Dectin-1 with NTHI in human airways may have an important impact on the pathogenesis of COPD.
Gesehen am 04.09.2020